"Shine & Click" Photo‐Induced Interfacial Unmasking of Strained Alkynes on Small Water‐Soluble Gold Nanoparticles. Issue 5 (22nd November 2016) - Luo, Wilson; Gobbo, Pierangelo; McNitt, Christopher D.; Sutton, Dewey A.; Popik, Vladimir V.; Workentin, Mark S.
Abstract: In this study, we report the design, synthesis, and characterization of small 3 nm water soluble gold nanoparticles (AuNPs) that feature cyclopropenone‐masked strained alkyne moieties capable of undergoing interfacial strain‐promoted cycloaddition (i‐SPAAC) with azides after exposure to UV‐A light. A strained alkyne precursor was incorporated onto AuNPs by direct ligand exchange of a thiol‐modified cyclopropenone‐masked dibenzocyclooctyne (photoDIBO) ligand. These photoDIBO‐AuNPs were characterized by 1 H NMR, IR, and UV/Vis spectroscopy, as well as transmission electron microscopy (TEM) and thermogravimetric analysis (TGA), and the extent of modification was quantified. Upon irradiation with UV‐A light, photoDIBO‐AuNPs underwent efficient and quantitative regeneration of the parent strained alkyne by photochemical decarbonylation to afford DIBO‐derivatized AuNPs. DIBO‐AuNPs were found to react cleanly and rapidly ( k =5.3×10 −2 m −1 s −1 ) by an interfacial strain‐promoted alkyne‐azide cycloadditon (i‐SPAAC) with benzyl azide, which served as a simple model system. Furthermore, DIBO‐AuNPs were reacted with various azides and a nitrone (interfacial strain‐promoted alkyne‐nitrone cycloaddition, i ‐ SPANC) to showcase the generality of this approach for the facile modification of AuNP surfaces and their properties. The cyclopropenone‐based photo‐triggered click chemistry at the interface of water‐soluble AuNPs offers exciting opportunities for the atom‐by‐atom control and assembly of functional materials for applications in materials and biomaterials science as well as in chemical biology. Abstract : Shiny & click chemistry : We report the design, synthesis, and characterization of small 3 nm water‐soluble gold nanoparticles that feature cyclopropenone‐masked strained alkyne moieties capable of undergoing interfacial strain‐promoted cycloaddition with azides after exposure to UV‐A light.